IMPLEMENTASI AKUNTABILITAS TERHADAP PENGELOLAAN ANGGARAN DI DEWAN PERWAKILAN RAKYAT KABUPATEN ACEH BARAT - Nila Trisna; Nodi Marefanda (Universitas Teuku Umar, 2017)
The purpose of this research is to know and to explain about the implementation of accountability for the management of the budget in the House of Representatives District (DPRK) Aceh Barat. This research uses nomative juridical method and nomative empirical. Research specifications are descriptive analytical mind. The data source that is used secondary data, through investigations books, official documents and research results of the experts in the form of reports. In addition to the collection of legal materials, also collected primary data that is done with how to perform the interview. The results of the study showed that the DPRK budget is a part that is not an inseparable part of the qanun Regency of Aceh Barat about APBK. The study also follows the discussion of the budget of other SKPK mechanism and discussed together between a team of Local Government Budget and Budget Committee DPRK. The realization of the Secretariat budget DPRK West Aceh good enough, almost all planned activities in 2016 can be implemented. DPRK budget supervision of West Aceh done by many parties, which is in addition to direct the Secretary of the DPRK authorities in West Aceh itself, also done by Inspektorat Jenderal, BPK district representatives of the province of Aceh and BPKP Aceh Province. It is recommended that the preparation of the Secretariat budget DPRK West Aceh on the future can be more is clarified again to prevent overlapping budget spending to one activity will be but with a different name. Keywords: Accountability, Budget Management and Planning